2014
DOI: 10.1159/000371734
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Fosfomycin against Uropathogens

Abstract: Background: In recent years, the rising rates of resistance to antimicrobial drugs among pathogens have caused great difficulty for clinicians treating infectious diseases. The aim of the study was to assess the curative effect of fosfomycin in treating urinary tract infections (UTIs) in China. Methods: We collected clinical isolates of UTIs to determine their susceptibility to fosfomycin by the agar dilution method and to analyze extended-spectrum β-lactamase (ESBL)-producing isolates by the double-disc metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…It has broad-spectrum activity, including MDR pathogens such as extended-spectrum beta-lactamase (ESBL) producers, carbapenem-resistant Enterobacteriaceae (CRE), and vancomycin-resistant enterococci (VRE) [6,7,8]. Fosfomycin is recommended as the first-line treatment for uncomplicated UTIs; however, published experience with fosfomycin in the USA is limited, which may lead to clinician reluctance regarding its use in comparison to alternative agents [3].…”
Section: Introductionmentioning
confidence: 99%
“…It has broad-spectrum activity, including MDR pathogens such as extended-spectrum beta-lactamase (ESBL) producers, carbapenem-resistant Enterobacteriaceae (CRE), and vancomycin-resistant enterococci (VRE) [6,7,8]. Fosfomycin is recommended as the first-line treatment for uncomplicated UTIs; however, published experience with fosfomycin in the USA is limited, which may lead to clinician reluctance regarding its use in comparison to alternative agents [3].…”
Section: Introductionmentioning
confidence: 99%
“…Fosfomycin tromethamine is an oral phosphonic acid derivative that was first discovered in 1969 [4]. Although the drug has been available for over four decades, its use in the United States has been limited, however it has been extensively tested and used in European and Asia [1,8,9,[11][12][13][14][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Several large in vitro surveys have looked at urinary tract infections and their causative organisms, such as E. coli [1,2]. It is clear now that E. coli has become increasingly resistant to most oral antibiotics including the fluoroquinolone class as well as to beta-lactam agents and trimethoprim-sulfamethoxazole [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid-mediated fosA enzymes are the most common mechanism of resistance in Enterobacterales. 49 In the USA, the fosA gene was detected in 80% of carbapenem-resistant K. pneumoniae isolates, 51 whereas in China, the fosA gene has been identified in only uropathogenic K. pneumoniae (26.7%) 52 and has not been recognized in any fosfomycin-resistant isolates in other studies. 50,53 Lastly, Mosime et al have reported that fosA enzymes are not a common cause of resistance amongst community-acquired urinary pathogens.…”
mentioning
confidence: 93%